To multiply the polynomial expression \((x+2)(x-4)\), we can use the distributive property (also known as the FOIL method for binomials).
\[ (x + 2)(x - 4) = x(x) + x(-4) + 2(x) + 2(-4) \]
Now, let's simplify that step by step:
- \(x \cdot x = x^2\)
- \(x \cdot (-4) = -4x\)
- \(2 \cdot x = 2x\)
- \(2 \cdot (-4) = -8\)
Now, combine all these:
\[ x^2 - 4x + 2x - 8 \]
Next, combine like terms:
\(-4x + 2x = -2x\)
So, we have:
\[ x^2 - 2x - 8 \]
Thus, the final expression is:
\[ 1x^2 + (-2)x + (-8) \]
So, filling in the blanks:
\((1)x^2 + (-2)x + (-8)\).